Brand personality in psychology career of state universities in Chile: a descriptive study - Denegri C., Marianela (2009)
The following research attempts to determinate the existence of a Brand Personality among two Chilean State Universities’ Psychology undergraduate programs. The Aaker’s Brand Personality Scale was applied on 289 students of both undergraduate programs in order to evaluate their impressions for 45 characteristics that are included in the scale. Results show the existence of a defined Brand Personality for each program, with one of them includes different characteristics. The advantage of a defined Brand Personality in a complex scenario for universities is discussed, including a reflection about the importance of stating differences on high education services.